The Effect of Financial Performance and Company Size on Stock Price with Dividend Policy as A Moderating Variable - Lisdawati Lisdawati (International Journal of Educational Administration, Management, and Leadership, 2023)
Research has been done with the title Effects of Financial Performance and Company Size on Stock Prices with Dividend Policy as a Moderating Variable (Empirical Study of Basic Industry and Chemical Companies Listed on the Indonesia Stock Exchange for the 2017-2021 period). The researcher took a sample of 20 companies on the Indonesia Stock Exchange. The purpose of this research is to prove the influence of Return on Assets, Current Ratio, Debt to Equity Ratio and Company Size both partially and simultaneously on Stock Prices moderated by Dividend Policy. Data analysis using Panel Data Regression and Moderating Regression Analysis (MRA). The results of the study found that Return on Assets had a significant positive effect on. Current Ratio has a significant negative effect on stock prices. Debt to Equity Ratio has a significant negative effect on stock prices. Company size has a significant positive effect on stock prices. Return On Assets, Current Ratio, Debt to Equity Ratio and Company Size together have a significant positive effect on stock prices. Dividend Policy is able to moderate the effect of Return on Assets on Stock Prices. Dividend Policy is able to moderate the effect of the Current Ratio on Stock Prices. Dividend Policy is able to moderate the effect of the Debt-to-Equity Ratio on Share Prices. Dividend Policy is able to moderate the effect of Company Size on Share Prices in Chemical and Basic Industrial Companies listed on the Indonesia Stock Exchange during the 2017-2021 period.